2018
DOI: 10.3390/nu10040454
|View full text |Cite
|
Sign up to set email alerts
|

ω-3 and ω-6 Fatty Acids Modulate Conventional and Atypical Protein Kinase C Activities in a Brain Fatty Acid Binding Protein Dependent Manner in Glioblastoma Multiforme

Abstract: Glioblastoma multiforme (GBM) is a highly infiltrative brain cancer with a dismal prognosis. High levels of brain fatty acid binding protein (B-FABP) are associated with increased migration/infiltration in GBM cells, with a high ratio of arachidonic acid (AA) to docosahexaenoic acid (DHA) driving B-FABP-mediated migration. Since several protein kinase Cs (PKCs) are overexpressed in GBM and linked to migration, we explored a possible relationship between B-FABP and levels/activity of different PKCs, as a functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…The atypical PKCζ has been proposed as a tumor suppressor because its depletion increases tumorigenesis in several types of cancers including GBM [ 148 ]. Additionally, PKCζ is postulated as a potential downstream effector of fatty acid-mediated alterations in GBM growth and migration [ 149 ]. Indeed, some authors associate PKCζ with migration: silencing of PKCζ impairs the phosphorylation of LIN-11, IsI1 and MEC-3 protein domain kinase (LIMK), which is important for actin polymerization, affecting migration and invasion in GBM [ 150 ].…”
Section: Protein Kinase C and Glioblastomamentioning
confidence: 99%
“…The atypical PKCζ has been proposed as a tumor suppressor because its depletion increases tumorigenesis in several types of cancers including GBM [ 148 ]. Additionally, PKCζ is postulated as a potential downstream effector of fatty acid-mediated alterations in GBM growth and migration [ 149 ]. Indeed, some authors associate PKCζ with migration: silencing of PKCζ impairs the phosphorylation of LIN-11, IsI1 and MEC-3 protein domain kinase (LIMK), which is important for actin polymerization, affecting migration and invasion in GBM [ 150 ].…”
Section: Protein Kinase C and Glioblastomamentioning
confidence: 99%
“…Increased levels of polyunsaturated fatty acid synthetase ELOVL2 (elongation of very long chain fatty acids protein) and cholesterol synthase 3-hydroxy-3-methylglutaryl-CoA reductase (HMGCR) were also found in GSCs, involved in the elongation of fatty acids, synthesis of membrane lipids and facilitation of EGFR signaling to support cell growth ( Wang X. et al, 2017 ; Gimple et al, 2019 ), and the impediment of fatty acid activator fatty acyl-CoA synthetase VL3 decreased the expression of stem-like phenotype CD133 and self-renewal functional molecules aldehyde dehydrogenase, musashi-1 and SOX2 on GSCs ( Sun et al, 2014 ). The brain fatty acid binding protein (B-FABP, FABP7) participating in the utilization of unsaturated fatty acids also acted as a risk factor to drive the migration and infiltration of glioma cells and the growth of GSCs ( Elsherbiny et al, 2013 ; Morihiro et al, 2013 ) dependent on the ratio of arachidonic acid (AA) to docosahexaenoic acid (DHA) ( Elsherbiny et al, 2018 ). Prostaglandin E2 (PGE2) is another unsaturated fatty acid and known as an inducer of inflammation and pain, which was catalyzed from AA by cyclooxygenase (COX)-2 and prostaglandin E synthase (PGES) overexpressed in glioma cells, especially mesenchymal cells ( Behnan et al, 2019 ).…”
Section: Metabolic Properties Of Glioma Cellsmentioning
confidence: 99%
“…Several studies have shown the involvement of PUFAs in modulating this process in brain cancer progression. For example, ARA and DHA have been shown to modulate cell proliferation, differentiation, and migration through PKC activities in a fatty acid-binding protein (B-FABP)-dependent manner in glioblastoma multiforme cells (U87) [ 86 ]. Besides this and contrary to what has been reported, Leaver et al showed that γ-linolenic acid (GLA) decreased proliferation both in vitro (C6 glioma cell line and multicellular glioma spheroids prepared from cell lines) and in vivo (implanted C6 glioma cells in rats) models through MTT assay and proliferating cell nuclear antigen (PCNA) and Ki-67 stain, respectively [ 87 ].…”
Section: Importance Of Pufas In Brain Functioning and Brain Cancermentioning
confidence: 99%